Power Distribution Network Reconfiguration by Using EPSO for Loss Minimizing - Sulaima, Mohamad Fani; Jali, Mohd Hafiz; Wan Daud, Wan Mohd Bukhari; Mohd Nasir, Mohamad Na'im; Jaafar, Hazriq Izzuan (Trans Tech Publications, 2014)
Due to the complexity of modern power distribution network, a hybridization of heuristic method which is called as Evolutionary Particle Swarm Optimization (EPSO) is introduced to identify the open and closed switching operation plans for network reconfiguration. The objectives of this work are to reduce the power losses and improve the voltage profile in the overall system meanwhile minimizing the computational time. The proposed combination of Particle Swarm Optimization (PSO) and Evolutionary Programming (EP) is introduced to make it faster in order to find the optimal solution. The proposed method is applied and it impacts to the network reconfiguration for real power loss and voltage profiles is investigated respectively. The proposed method is tested on a IEEE 33-bus system and it is compared to the traditional PSO and EP method accordingly. The results of this study is hoped to help the power engineer to configure the smart and less lossed network in the future.